Single strand conformation polymorphism in keratin associated protein (KAP7) gene in carpet wool breeds of indigenous sheep - Geetu Malik; JS Rana; SC Gupta; Neelam Gupta (Journal of Livestock Biodiversity, 2025)
The major components of wool and goat fibre are the keratin proteins, which are largely responsible for their structural and mechanical properties. Keratin proteins are widespread in nature, being found in the nuclei and cytoplasm of almost all differentiated eukaryote cells. This study was carried out in five diverse sheep breeds; viz. Karnah and Gurej from Jammu and Kashmir, Gaddi from Himachal Pradesh (cold arid zone) and Malpura and Jaiselmeri from Rajasthan (hot arid zone). In KAP 7.0 gene PCR product amplicons developed by using forward primers (5’-ACT TGC TCT TCA CAT TCT ATC-3’) and reversed primers (5’-GGT TCG CCG TAG TCA TCT G-3′) of approximate size of 334 bp of complete CDs from 352 to 685 nucleotide positions in different breeds. For this gene a large variation (3-9 haplotypes) was observed in different breeds of which AA haplotype was most abundant in all breeds.